Rancang Bangun Sistem Pendukung Keputusan Penilaian Karyawan Terbaik Pada PT. Surya Toto Indonesia, Tbk Menggunakan Metode Simple Additive Weighting (SAW) Berbasis WEB - Taufiq, Rohmat; Hambali, Ahmad; Saifudin, Aries (Jurnal Informatika Universitas Pamulang, 2021)
PT. Surya Toto Indonesia is a large company in Banten Province. This company is located on Jl. MH. Thamrin km. 7, Tangerang Banten. Until now, the number of employees is around 1.200 employees. With a large number of employees, a proper performance appraisal decision support system is needed so that the work results of employees can be clearly and well defined. Until now, the process for performance appraisal is still using paper or also called manual which causes the process to take a bit longer and reports cannot be enjoyed in real time. From the existing problems, a web-based decision support system is needed which will be able to facilitate all parties related to the performance appraisal process. The method used begins with communication with the parties involved. Furthermore, planning, the process of data collection, analysis, planning, and finally reporting is carried out. The conclusion from this suggests that using the existing criteria provides two more criteria. By giving weights and calculations performed on three employees, the score obtained for employee C got the highest score (0.92) followed by employee B, and the lowest score (0.84) was employee A.